Compressive behavior and constitutive model of polyurea at high strain rates and high temperatures. (March 2020) - Liu, Qiang; Chen, Pengwan; Zhang, Yang; Li, Zhirong
Abstract: To study the dynamic compressive mechanical properties of polyurea at strain rate range of 1400 s −1 –5700 s −1 and high temperature range of 20 ℃–80 ℃, we conducted a dynamical mechanical experiment utilizing a split Hopkinson pressure bar (SHPB) system. The compressive stress-strain curves of polyurea under various strain rates and temperatures are analyzed and discussed. The experimental results indicated that the strain rate and high temperature can remarkably influence the mechanical behaviors of polyurea, compression behaviors increased with the increasing of strain rate and compression behaviors decreased with the increasing of temperature. In addition, a thermal-visco-hyperelastic constitutive model based on five-parameter Mooney-Rivlin model was proposed to describe the compression stress-strain behavior of polyurea over a wide range of strain rates and temperatures. The model parameters were obtained by fitting the experimental stress-strain curves. The model prediction results show good agreement with the experimental results.